Sragen Government's Business Communication Strategy for Economic Empowerment and Poverty Alleviation - Astuti Itasari, Andri; Widiyowati, Estu (Borong Newinera Publisher, 2026)
This study aims to analyze the business communication strategy of the Sragen Regency Government in building multi-sector collaboration for community economic empowerment as an effort to address extreme poverty. The research method used is a case study with data collection techniques through in-depth interviews with stakeholders, non-participatory observation on the implementation of the Village Completed Poverty program, and analysis of policy documents and program reports. Data analysis techniques use descriptive analysis to identify patterns of business communication strategies, while data validity is strengthened by triangulation from various sources. The results of the study indicate that the implemented business communication strategy is based on the principles of two-way communication, openness, and transparency carried out through formal forums and direct interactions with the community. Cross-sector collaboration involves regional apparatus organizations, village governments, the business world, the private sector through social responsibility programs, and philanthropic institutions with mutual cooperation support. The implementation of this strategy is able to strengthen the Village Completed Poverty program by providing business capital assistance, skills training, the provision of productive tools, and facilitation of education and basic infrastructure. The research findings show a significant decrease in the number of extremely poor families in the target villages and an increase in the economic independence of the beneficiary community. The conclusion of this study is that the success of economic empowerment and extreme poverty alleviation in Sragen Regency is very much determined by the optimization of business communication strategies that build trust, participation, and synergy between stakeholders.